The development of an artificial energotechnological process with the induced heat and mass transfer - Pogozhikh, Micola; Pak, Andrey (Eastern-European Journal of Enterprise Technologies, 2017)
The study justifies the importance of developing “artificial” energy technology processes. The “start-up” of these processes under natural conditions does not meet the conditions for the processes that are truly natural. For “artificial” processes, it is common that at least one or more parameters or properties of the system can have no “affinity” with the environment. The system properties may acquire the equilibrium value only after overcoming some energy activation barrier. One of these new artificial processes is a process of an induced heat and mass transfer (InHMT). The aim of the study is to determine the necessary and sufficient conditions as well as to develop balance equations for technical applications of the InHMT process, based on generalizing theoretical and experimental data obtained so far. The phenomenon of the “artificial” energy technology process of InHMT is observed in a thermostat. The InHMT process consists in inducing an intensive removal of the liquid phase from the thermostat volume as well as in an intensive dissipation of heat while the system in moving from an unstable equilibrium to a stable equilibrium. Balance equations for the InHMT effect have been developed on the basis of the observed facts in the case of fluctuations in the concentration of particles in a continuous gaseous medium inside the thermostat due to fluctuations of the concentration of particles in the volume of the obturator under the impact of an external continuous gas medium. These equations have helped determine that the heat, which is dissipated during the InHMT process due to the removal of the mass flow into the environment, depends on the physical properties of the liquid, the way of filling the thermostat volume, and the structure of the obturator.